MANAJEMEN KEDISIPLINAN SANTRI PPS AN NASHAR KECAMAN BATU AJI KELURAHAN KIBING KOTA BATAM - Defi Saputra (UNISAN JURNAL, 2024)
This exploration means to assess the execution of Islamic training the executives in working on the discipline of understudies in Islamic life experience schools. This examination involves an unmistakable strategy with information assortment procedures as perception, meetings and documentation studies. The respondents for this examination were understudies and showing staff at one of the Islamic life experience schools. The consequences of the exploration show that the execution of Islamic training the executives in Islamic live-in schools has made a positive commitment in working on the discipline of understudies. Getting ready successful instructive projects, clear instructive targets, choosing suitable learning strategies, assessing understudy learning results and execution, as well as training and guiding are key elements in carrying out Islamic instruction the executives at the A Nashar Islamic Live-in School. Notwithstanding, there are as yet a few snags in executing Islamic training the executives in Islamic live-in schools, for example, an absence of satisfactory offices and foundation, negligible accessibility of reference books, and an absence of value educators. Thusly, further endeavors are expected to work on the nature of execution of Islamic training the executives in Islamic live-in schools, like further developing offices and framework, working on the nature of educators, and expanding admittance to reference books for understudies.